High frequency of larval abnormalities of the toad Rhinella arenarum (Anura: Bufonidae) in an Argentinian agroecosystem - Sansiñena, Jesica A. (2023)
Introduction: The frequent use of pesticides is currently considered a cause of environmental pollution due to the high rate of entry of these substances into agroecosystems. This constitutes a risk for the species that inhabit these ecosystems, in particular anurans whose characteristics make them prone to exposure to and interaction with environmental pollutants. Objective: To report the occurrence of abnormalities in larvae of the common toad Rhinella arenarum inhabiting ponds surrounded by agroecosystems. Methods: In two consecutive springs (2015 and 2016), reproductive events of common toads were monitored in temporary pond systems in agricultural and non-agricultural areas, located near the city of La Plata (Buenos Aires, Argentina). The physicochemical parameters of the ponds were measured, and the stage of each reproductive event was recorded, such as the numbers of adult toads, amplexus and clutches. In the laboratory, the larvae were measured and photographed, their stage of development was recorded, and their morphology was examined under a stereomicroscope. Representative samples (normal and abnormal) from each pond studied were processed for histopathological analysis. Results: In the field studies carried out on a population of R. arenarum collected in an agroecosystem, a lower number of reproductive adults and clutches were observed in relation to the population of a non-agricultural pond. A total of 1 910 larvae were collected: 529 and 1 381 larvae from ponds located in non-agricultural and agricultural areas, respectively. Larvae from the agroecosystem showed two types of abnormalities: severe tail flexure and abdominal bloating. In addition, five degrees of severity could be determined in relation to abdominal bloating. Conclusions: This work reports the high frequency and severity of abnormalities observed in the early stages of R. arenarum larvae living within an agroecosystem, providing evidence of the negative impact that agricultural activities cause on aquatic ecosystems surrounded by farming areas.